The other Israel with host Ted Pike - Pike, Ted.; Pike, Elizabeth Alynn (Oregon City, Or. : National Prayer Network, 1987)
The video is about Rabbinical teachings concerning the position of gentiles, Christians and Christianity in the Jewish world, the Jewish diaspora, and the present day Israel; a land full of strife.
Keywords: Talmud; Christians in Rabbinical literature; Judaism -- Relations -- Christianity; Jewish-Arab relations